The Philosophy of Meugang Tradition in Acehnese Society: A Cultural Study - Khalda Sajida Mulyadi; Nurmahni Harahap (Winaya Inspirasi Nusantara Foundation, 2024)
Meugang is a tradition that has been preserved by the people of Aceh until today. Meugang is the slaughtering of cattle or buffalo, but in the Pidie Jaya area, they prefer buffalo as the animal slaughtered on Meugang Day. Meugang tradition is also a philosophy of cooking meat and gathering with family and close relatives. Meugang is held when welcoming the months of Ramadan, Eid al-Fitr, and Eid al-Adha. Meugang tradition is believed to be a very important thing and should not be abandoned for the people of Aceh. This Meugang tradition is celebrated by all levels of society, both in villages and cities. This Meugang tradition has been carried out for hundreds of years in Aceh. Meugang began in the Kingdom of Aceh during the time of Sultan Iskandar Muda.